Insecure attachment and lower preference for romantic relationship nostalgia predict higher acceptance of infidelity. (March 2023) - Swets, Julie A.; Cox, Cathy R.
Abstract: Recent research on relationship nostalgia, a sentimental longing for the past of one's romantic relationship, has shown to improve commitment, which should protect against infidelity intentions. However, previous research has shown that more insecurely attached persons do not reap the same benefits from the emotion of nostalgia. The current work introduced the concept of relationship nostalgia preference (i.e., the extent to which people would like displays of nostalgia from their romantic partners [e.g., feeling safe and secure like in earlier parts of the relationship]). In Study 1, nostalgia preference's associations with attachment style and relationship quality (satisfaction, etc.) were tested, revealing negative correlations with attachment avoidance and positive correlations with relationship quality. In Study 2, a conditional process model exhibited how avoidant attachment predicted lower nostalgia preference (replicating Study 1), which was related to reduced commitment. Commitment reduction, in turn, predicted higher attitudes toward infidelity and intentions to commit infidelity. Overall, when people are more avoidantly attached, they like relationship nostalgia less, which has downstream negative consequences for their partnerships. Highlights: Stronger preference for relationship nostalgia is linked to higher relationship quality. More avoidantly attached people have a lower preference for relationship nostalgia. More anxiously attached people have a higher preference for relationship nostalgia. Lower relationship nostalgia preference carries over to lower partner commitment. Lower relationship nostalgia preference also predicts more approval of infidelity.